OP11 Assessing models of ACP in primary care, the meta-LARC trial: part 5: planning and supporting implementation. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Dorr, D; Michaels, L; Izumi, S; Shankle, N; Strauss, S
Abstract : Background: Implementation of ACP is challenging, requiring a multi-pronged approach in primary care. We sought to provide a toolkit that would facilitate practices' adoption of the Serious Illness Care Program, as a means of improving the quality of care and engaging patients in serious illness care discussions and planning. Methods: The joint coordinating center established a working committee to compile implementation resources. We used an iterative approach to identify key issues, materials, and discussion points necessary to engage practices in ACP implementation. We involved stakeholder groups representing patients, clinicians, practice facilitators, researchers, and informaticians. The group identified, adapted, and reached consensus on materials and approaches to facilitating ACP in primary care practices. Results: We identified potential implementation barriers, including knowledge, attitudes, workflow, health information technology constraints, and sensitivity of the topic to engaging practices in ACP. We gathered materials to address these barriers including checklists, adaptable templates for dissemination and documentation, and developed a guide to facilitate conversations with practices. The key topics included practice readiness, patient identification, use of prognostic algorithms, workflow enhancement, effective documentation, and sustainability. We are using the TiDier checklist to monitor implementation fidelity to the ACP models in the trial. Conclusion: We created a toolkit to support implementation of ACP in primary care practice that can be used by practice facilitators. It covers the major topics identified by stakeholders as essential for ACP implementation. We will evaluate and revise this, making an enhanced implementation guide available to the trial practices as well as to others.